The Influence of Leadership Style, Work Motivation, and Work Stress on Performance - Wahyuningsih, Yuli; Eko Soetjipto, Budi; Restuningdiah, Nurika; Syihabudhin (International Journal of Science, Technology & Management, 2021)
Human resources are the most important asset in a company or organization because of their role as the subject of implementing policies and operational activities of the organization. The purpose of this study is to describe the leadership style, motivation, and work stress on employee performance. The population in this study amounted to 30 respondents to the service employees at the hospital. Data collection techniques used were distributing questionnaires and interviews. The analytical tool in this study with a description of the analysis and multiple linear regression. The results showed that leadership style affected employee performance, work motivation affected employee performance, and job stress affected employee performance. The result of the coefficient of determination is 0.749. Therefore, employee performance is influenced by the variable leadership style, motivation, and work stress by 74.9%. Meanwhile, the remaining 25.1% is influenced by other variables not included in the research model. Multiple correlation coefficient (R) (multiple correlations) describes the strength of the relationship between variables. In this study, this value was 0.866. This means that the relationship between all independent variables and the dependent variable is a very close relationship